The effect of Laproxide L-303 on connective tissue metabolism under prolonged subtoxic exposure (Environment & Health, 2015)
Objective. We studied a prolonged subtoxic effect of triglycidyl ether of polyoxypropylene triol on the indices of connective tissue metabolism under conditions of subacute experiment.Materials and methods. Triglycidyl ether of polyoxypropylene triol with molecular weight of 303 with the regulated physical-and-chemical properties, that is an epoxide-containing oligoether with ,,Laproxide" (L-303) brand name, was a subject of the research. According to the experi- ment conditions, daily in the morning for 45 days prior to feeding the animals were administered, using a metallic tube, the peroral water solutions of Laproxide L-303 in the doses of 1/10, 1/100, 1/1000 DL50 respectively, 575.0; 57.5; 5.75 mg/kg of the body. The rats in the control group were administered a corresponding amount of drinking water. Following the completion of subacute experiment the content of glycosaminoglycans, elastase activity and collagenolytic activity were assessed in blood plasma.Results. The results of a given xenobiotic effect of 1/10, 1/100 DL50 on white rats showed a significant increase in elastase activity, collagenolytic activity of blood plasma as well as in the content of glycosaminoglycans. L-303 in these doses is capable to disrupt an intracellular metabolism, to accelerate the aging of the body, to form the immune deficiency and remote consequences of their impact. Triglycidyl ether of polyoxypropylene triol of 1/1000 DL50 did not affect the indices of connective tissue metabolism.
Keywords: xenobiotics; laproxide; oligoether; connective tissue